Pengaruh Latar Belakang Jurusan dan Minat Belajar terhadap Hasil Belajar Siswa Kelas XI pada Mata Pelajaran Biologi di SMA IT Granada Samarinda - Azzahra, Salma; Rambitan, Vandalita Maria Magdalena; Turista, Dora Dayu Rahma; Makkadafi, Suparno Putera; Akhmad, Akhmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the effect of major background and learning interest on the learning outcomes of grade XI students in Biology at SMA IT Granada Samarinda. The background of this study is based on the importance of understanding internal and external factors that can influence student academic achievement, especially in subjects that require high-level thinking skills such as Biology. This study uses a non-experimental quantitative approach with an ex post facto method and multiple linear regression analysis techniques. The instrument used is a closed Likert-scale questionnaire that has been tested for validity and reliability. The sample consisted of 55 students selected using a purposive sampling technique. The data were analyzed using prerequisite tests (normality, multicollinearity, and heteroscedasticity), then processed with the help of the SPSS version 25 program at a significance level of 5%. The results showed that both major background and learning interest significantly influence student learning outcomes, both partially and simultaneously. The coefficient of determination (R2) value of 47.3% indicates that variations in student learning outcomes can be explained by the two independent variables. These findings indicate that selecting a major that aligns with the subject's characteristics and fostering learning interest can be effective strategies for student learning outcomes in Biology.